(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Pharmacy practice is still in the initial stages of development in India, but the launching of Doctor of Pharmacy (PharmD) study program has brought serious discussions about clinical pharmacy in the country. As the profession is in a budding stage in the country, the patients, physicians, nurses, other healthcare providers, recruiters in pharmaceutical industries, prospective students, and their parents have numerous questions about this profession and study course. The objective of this article is to create awareness about clinical pharmacy services and to introduce the role of clinical pharmacists. After reading this article, one will know about the usefulness of clinical pharmacists in the Indian healthcare system against the current laws in the system. The article describes the role of Clinical pharmacist in the hospitals, and it also tells about the related myths and facts. A Pharm D person is an eligible to work in all areas where a Bachelor of Pharmacy (B. Pharm) qualified student can work. Apart from this, a clinical pharmacist (both Pharm D and M. Pharm Pharmacy Practice) can work in several other areas after completion of the course. Here, we are predicting the career prospectuses and job opportunities of Clinical Pharmacists according to the international scenario. Though all these areas are not well-established at present in India for clinical pharmacists, we believe that these areas would be open for them in near future. The article describes the role of clinical pharmacists in the hospitals, in research, in pharmaceutical/contract research companies, in community service and it also tells about the related myths and facts. Prospective job opportunities for clinical pharmacists, present challenges and the possible solutions are elaborated as well.